Mapping the Potential to Establish Multifunctional Agrofood Parks to Foster the Food Transition at a Regional Level - Rosário Oliveira; Gabriel Spínola Garcia Távora (Land)
Food transition has been widely inspiring regional and local food system transformation strategies to accomplish the Sustainable Development Agenda goals. Considering the urgency required to transform food systems by 2030, actions should be supported by principles of science-based and practical effectiveness. Within the framework of the Food Transition Strategy for the Lisbon Metropolitan Area (FTS-LMA), a methodology to identify the potential to establish Multifunctional Agrofood Parks (MAPs) has been applied to inform decision-makers where this potential is located as an opportunity to transform local food system towards healthier and more affordable food production. The method uses an Analytical Hierarchy Process (AHP) operated in a Geographic Information System (GIS) to integrate a multicriteria environment and socioeconomic variables for determining suitable territories for MAP implementation. The results show the higher suitability for the MAP establishment in the LMA is over 30% of the region, which drives a thorough reflection on how to set up a socio-territorial transformation of the metropolitan food system envisioned by the FTS-LMA by using current results as part of a food system planning exercise to determine where the ecological suitability for sustainable food production overlap with the capacity for intervention by the fabric of producers in each of the 18 municipalities.